Malnutrition and the presence of intestinal parasites in children from the poorest municipalities of Mexico - Javier Gutierrez-Jimenez; Maria G C Torres-Sanchez; Leamsi P Fajardo-Martinez; Maria A Schlie-Guzman; Lorena M Luna-Cazares; Alma R Gonzalez-Esquinca; Salvador Guerrero-Fuentes; Jorge E Vidal (Journal of Infection in Developing Countries)
Background: For many years Chiapas, Mexico's poorest state, has had the highest rate of child mortality due to intestinal infections of unknown etiology in the country. To begin identifying the infectious agents, our work determined the prevalence of intestinal parasites as well as malnutrition in children from Chiapas's three most impoverished municipalities: Pantepec, Chanal, and Larrainzar. Methodology: In this cross-sectional study, conducted between January and November 2009, we assessed the prevalence of intestinal parasites by means of coproparasitological analysis in children <5 years of age (N=250) from three of the marginalized municipalities: Pantepec, Chanal and Larrainzar. The prevalence of malnutrition was then assessed using the Mexican official norm NOM-031-SSA2-1999 and WHO criteria. We evaluated the association between age (breast-fed and pre-school children) with parasites and nutritional status. Results: Our analysis revealed the highest prevalence of intestinal parasites in children from Pantepec (62.8 %), followed by Chanal (47.3 %), and then Larrainzar (11.9 %). The nematode Ascaris lumbricoides was the most prevalent enteroparasite (33.6%). Anthropometric analysis revealed that >40% of children represented varying degrees of malnutrition and a marked constitutional delay in growth. A very high prevalence of stunting was also recorded in children from Chanal and Larrainzar (70% and 55 %, respectively). An association between infection with intestinal parasites and malnutrition was observed in Pantepec. Preschool-age children were more likely to be infected with intestinal parasites. Conclusion: Our results indicate the urgent need for interventions in order to 1) improve the nutritional status of children and 2) reduce infection rates of enteric parasites.